Los ejes DOC una estrategia conceptual y metodológica en la construcción del Conocimiento Profesional del Profesor - Fonseca Amaya, Guillermo (Revista Científica, 2018)
The science’s didactic as a discipline in consolidation, is built through several lines of research, including The Professional Knowledge of the Teacher, which arises because of the need to understand how teachers in training and in the exercise of a unique knowledge of their profession. The DOC Axes (Dynamic, Obstruction and Questioning), constitute a conceptual and methodological device of reflexive order on the aspects that are articulated in the construction of the Professional Knowledge of the Professor. Accordingly, the results of an IA process are presented, where a teacher in training, understands that Evaluation and Teaching Strategy (School Research), are constituted in Axes DOC which contribute in their training process as biology’s teacher. Derived from the case study it is possible to show two characteristics of the DOC Axes (Dynamic, Obstruction and Questioning) the temporal coexistence of the axes on a knowledge and the possibility of its transformation. Thus, it is considered that the Axes DOC, is a conceptual proposal that not only in the didactic research, but also in the formative processes, makes contributions both in the understanding and in the transformation and enrichment of professional knowledge.